Market leader - Rogers, John (Pearson education,Longman, 2005)
This gives extra practice in the areas of grammar and vocabulary, together with a complete syllabus in business writing Students work with text models and useful language, then do a writing task to consolidate the learning Provides regular self-study pronunciation work with audio CDs or cassettes and exercises